3D STATIC RESERVOIR MODELING AND HYDROCARBON RESERVE ESTIMATION IN BINIO FORMATION, RASGAR FIELD, CENTRAL SUMATRA BASIN, RIAU - Adiva, Miranda
Rasgar Field is a natural gas field located in Tenayan Raya District, Pekanbaru City, Riau Province and is situated in the Central Sumatra Basin with an area of approximately 120 km2. In this field, 3D static reservoir modeling is required before estimating hydrocarbon reserves as a guide for its field development. The focus of research and modeling are in B3e reservoir and B4 reservoir in the Binio Formation. Therefore, this research aims to understand the regional geology and field geology of the study area and determine the reservoir characteristics that includes facies, stratigraphic correlation, reservoir geometry and properties, as well as estimate the hydrocarbon reserves. Data available are wireline logs and petrophysical analysis results from 6 wells, 1 checkshot data, 19 of 2D seismic lines, and descriptions of 11,15 meters of core from an analog well located 30 km away from the study. The 3D static reservoir modeling was carried out using Sequented Indicator Simulation (SIS) and Sequented Gaussian Simulation (SGS) methods using well data and trend modeling in the form of facies probability maps. Reserve estimation was then carried out based on the result of the 3D static reservoir modeling. Based on the analysis of core samples, six lithofacies can be determined, including fine grain sandstone with bioturbation (Sbh), medium grain sandstone with bioturbation (Sbk), fine grained sandstone with wavy bedding (Swh), medium grain sandstone with wavy bedding (Swk), massive clay with bioturbation (Mb), and clay with parallel lamination (Ml) in the Binio Formation in the study area. The depositional environment in the study interval is a tidedominated estuary with facies architecture (facies association) including Intertidal Bar, Subtidal Bar, and Muddy Subtidal. The geological structures consist of NW-SE trending anticlinal ridges bounded by reverse faults on its limb. The deposition of shaly-sandstone in this reservoir is interpreted to occur in the same direction. The volumetric calculation of the hydrocarbon reserves in the B3e and B4 reservoir intervals yielded results of 18,9 BCF and 6,1 BCF, with a combined total of 25 BCF.